Complete Androgen Insensitivity Syndrome with Sertoli Cell Adenoma: A Case Report and Review of Literature (Nepalese Journal of Radiology, 2012)
Complete androgen insensitivity syndrome is a rare X-linked recessive disorder. In patients with this syndrome, testicular tumors, especially seminoma, may develop after puberty. Gonadal malignancies like sertoli cell tumor, yolk sac tumor; embryonic teratoma and unclassified sex cord stromal tumor are rare in these patients. We present here, a case of complete androgen insensitivity syndrome with sertoli cell adenoma in a 25 years old patient who presented to us with history of primary amenorrhoea and bilateral inguinal swellings and was managed with bilateral gonadectomy.DOI: http://dx.doi.org/10.3126/njr.v1i1.6327 Nepalese Journal of Radiology Vol.1(1): 61-64